Focus on the dabrafenib, vemurafenib, and trametinib in the clinical outcome of melanoma: A systematic review and meta-analysis - Ida Ayu Widya Anjani; Anak Agung Bagus Putra Indrakusuma; I Gede Krisna Arim Sadeva; Putri Ayu Wulandari; Luh Made Mas Rusyanti; Prima Sanjiwani Saraswati Sudarsa; I Gede Putu Supadmanaba; Desak Made Wihandani (Explorer Front, 2020)
Background: Melanoma is the most severe lethal skin cancer, affecting melanin producer cells (melanocytes). Surgery is the most common treatment, whereas, for the advanced stage, the development of treatment is recommended. BRAF (Dabrafenib and Vemurafenib) inhibitor or MEK inhibitor (Trametinib) is the most frequently targeted melanoma therapy due to more than 80% of patients with positive BRAF mutation. In this review, those treatments will be investigated systematically to identify their clinical outcome. Method: This systematic literature review (SLR) was performed from Cochrane, Science Direct, Google Scholar, and Pubmed. Cochrane Risk-of-Bias Tool RoB2 is used to assess RCT studies and New-castle Ottawa Scale Assessment to assess cohort studies by three different assessors. Data analysis was carried out by using Review Manager (RevMan 5.4). Heterogenicity test was assessed by I2 and Chi2 statistic Result: There are 20 studies used in this article (13 RCT and seven cohorts). The overall survival (OS) and progression-free survival (PFS) of the survey that using targeted therapy (vemurafenib, trametinib, or dabrafenib) compare other treatments (chemotherapy, immunotherapy, etc.) showed risk ratio (RR) was 1.12 (95%CI 1.07,1.17; I2=100%; p<0,00001). The OS and PFS with monotherapy compare of vemurafenib, trametinib, or dabrafenib with combination therapy showed RR was 1.09 (95%CI.06,1.13; I2=99%; p<0,00001). Conclusion: BRAF and MEK targeted therapy has a good prognosis for a patient with a positive BRAF gene mutation and could be combined with other treatments for better clinical outcomes rather than monotherapy.